INFLUENCE OF SIGNAL-TO-NOISE RATIO ON EDDY CURRENT SIGNALS OF CRACKS IN STEAM GENERATOR TUBES - HUR, DO HAENG; CHOI, MYUNG SIK; SHIM, HEE-SANG; LEE, DEOK HYUN; YOO, ONE (Nuclear engineering and technology, 2014)
This work presents the influence of noise originating from the tube itself on the detectability and sizing accuracy for laboratory-induced outer diameter axial cracks in nuclear steam generator tubes. The variations of signal amplitude and phase angle of the same cracks were analyzed when increasing the signal-to-noise ratio of the tube itself from 9 to 18. It was experimentally verified that the detectability for small cracks was enhanced by increasing the signal-to-noise ratio. The phase angle also rotated to a value representing the actual position and depth of a crack when increasing the signal-to-noise ratio.